Mobile health apps for pregnant women usability and quality rating scales: a systematic review - Mohammad Reza Mazaheri Habibi; Fateme Moghbeli; Mostafa Langarizadeh; Seyed Ali Fatemi Aghda (BMC, 2024)
Abstract Objective This study is to identify the apps used by pregnant women during the technology era and to choose the best app from the point of view of pregnant women and experts. Methods The article is a research article that uses PRISMA flowchart. Given that there are many apps in the field of pregnancy and due to technological advances, the articles of the last 13 years that have been scientifically published in the databases of Google Scholar, PubMed, and Science Direct have been analyzed. The most widely used and, at the same time, the best app is introduced in terms of its high usability in users' attitude. Finally, Apps will be compared in terms of accuracy, precision, and usability of the dimensions of Jacob Nielsen's five principles. Results According to the search strategy, 23 articles were identified qualitatively by reviewing both authors. Then, the types of apps were divided into three general categories, pregnant entertainment apps, pregnant information apps, and monitoring apps for mothers' physical health. Finally, 10 apps were selected and the Amila app was introduced as the best due to its high usability (Effectiveness %66.66) and users' satisfaction or women's choice (%98). Conclusion Using trusted apps to maintain their health and reduce traffic will be very important. Given that this research article was written with the aim of choosing the best app, that not only provides the required information to mothers, but also the ability to interact with doctors and specialists.